Unusual clinical picture of food-dependent exercise-induced anaphylaxis associated with soybean allergy and a reverse sequence of causative factors - Radlińska, Anna; Gomułka, Krzysztof; Zaleska, Anna; Mędrala, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Food-dependent, exercise-induced anaphylaxis (FDEIA) is a distinct form of food allergy associated with anaphylaxis, in which clinical symptoms are elicited only when two factors coexist – intake of sensitizing food with subsequent physical exertion. It was first described by Maulitz et al. in 1979 [1]. The pathomechanism of FDEIA remains to be the subject of research, especially the relevance of physical exertion in the elicitation of IgE-mediated systemic allergic reaction [2]. Most patients experience their symptoms after postprandial exercise (the typical sequence) [3]. Our team was the first who presented the case of FDEIA with atypical episodes when anaphylaxis occurred after exercise, followed by ingestion of the sensitizing allergen [4].